UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN ANTING-ANTING (Acalypha australis L.) PADA MENCIT YANG DI INDUKSI KARAGENIN 1% - Novita Sari; Samsuar Samsuar; Cindi Liyana (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Inflammation is the body's defense mechanism in response to tissue injury and disturbance by external factors. Anting-anting leaf (Acalypha australis L.) contain flavonoids and tannins suspected to have antiinflammatory activity.This study aims to examine the antiinflammatory activity of Anting-anting leaf (Acalypha australis L.) ethanol extract in mice induced by carrageenin 1%. Anti-inflammatory activity test was carried out using twenty-five (25) mice and each mice was induced using 1% carrageenin subplantarly. The mice were divided into 5 groups, group I as the negative control was administered 1% Na-CMC suspension, group II as the positive control was administered mefenamic acid 65 mg/kg BW, groups III, IV and V as the treatment group were administered 83, 166 and 332 mg/kg BW of Anting-anting leaf (Acalypha australis L.) ethanol extract. Inflammation volume was measured using a caliper every 60 minutes for 6 hours. Data were analyzed statistically using ANOVA (Analysis of variance). The results showed the Anting-anting leaf (Acalypha australis L.) ethanol extract 83, 166 and 332 mg/kg BW had anti-inflammatory activity, respectively (47.39 ± 1.7), (59.53 ± 0.9) and (50.56 ± 0.3)% in mice induced by carrageenin 1%. The ANOVA test showed there was a significant difference to the negative control. Based on the results of the study, it can be concluded that the ethanol extract from Anting-anting leaf (Acalypha australis L.) ethanol extract has anti-inflammatory activity with an effective dose of 332.28 mg/kg BW. Keywords: Anti-inflammatory, Anting-anting leaf, Acalypha australis L., carrageenin